2013
DOI: 10.1097/sla.0b013e318281b824
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Histological Subtype Classification of Intraductal Papillary Mucinous Neoplasms (IPMN) by Pancreatic Juice Cytology With MUC Stain

Abstract: Preoperative PJC with MUC stain proved to be highly reliable for identifying the histological subtype of IPMN and may provide useful information for deciding surgical indication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…Interestingly, classification of IPMN subtypes has been attempted preoperatively through immunohistochemical studies of pancreatic juice cytology by Hara et al 28 Histological IPMN subtype diagnosed with pancreatic juice cytology was compared with the subtype diagnosis made at resection. With the use of MUC1, MUC2, and MUC5AC immunostains, the histological IPMN subtype was correctly diagnosed in 89% of cases (32/36) with a sensitivity and specificity of 86 and 100%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, classification of IPMN subtypes has been attempted preoperatively through immunohistochemical studies of pancreatic juice cytology by Hara et al 28 Histological IPMN subtype diagnosed with pancreatic juice cytology was compared with the subtype diagnosis made at resection. With the use of MUC1, MUC2, and MUC5AC immunostains, the histological IPMN subtype was correctly diagnosed in 89% of cases (32/36) with a sensitivity and specificity of 86 and 100%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that several predictors for development of concomitant PDAC: older age >70 years [16], elevated serum CA19-9 level or worsening of diabetes [17]. Recently, Ideno et al reported gastrictype IPMN without GNAS mutation [22] as a predictor, which could be assessed preoperatively [23,24].…”
Section: Q9mentioning
confidence: 96%
“…Finally, recent advances with histological subtyping in combination with endoscopic techniques are allowing for what may be a reliable means of preoperatively risk stratifying patients [50] . Pancreatobiliary type IPMNs usually affect the main duct and demonstrate higher rates of high-grade dysplasia, higher rates of malignant transformation and higher rates of recurrence, even when resected as non-invasive neoplasms.…”
Section: Discussion: Who Should Undergo Tp For Ipmn?mentioning
confidence: 99%
“…Preoperative identification of pancreatobiliary or intestinal type would be beneficial for risk stratification and planning the type and extent of resection best suited for a patient. In a recent study by Hara et al [50] , histological subtype was successfully diagnosed preoperatively by pancreatic juice cytology with MUC stain in 89% (32 of 36; p < 0.01). The sensitivity, specificity and overall accuracy of this method were 86, 100 and 94% for intestinal subtype, respectively.…”
Section: Risk Factors For Recurrence Margin Statusmentioning
confidence: 99%